SPE International Symposium on Oilfield Chemistry 2013
DOI: 10.2118/164064-ms
|View full text |Cite
|
Sign up to set email alerts
|

Solids-Free Fluid Loss Pill for High Temperature Reservoirs

Abstract: The leakage of reservoir fluids into a wellbore during perforation, workover, or other completion operations is a substantial concern, especially in high temperature wells where existing fluids utilized to mitigate reservoir fluid influx offer poor performance. To maintain the hydrostatic integrity of the wellbore during these operations, a thermally-stable, solids-free fluid loss pill has been developed.The pill is composed of synthetic polymers and cross-linkers in monovalent high-density brine. Under ambien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Among them, polymer gel plugging agent is an important branch of chemical gel plugging agent, compared with general plugging materials. The advantages are obvious, with: (1) low density is beneficial to the protection of oil and gas reservoirs; (2) gelling time is controllable, and the controllable time range is large, which is convenient for it to accurately reach the missing layer for plugging; (3) plugging The leaking slurry has strong fluid loss performance, and the formation of filter cakes can help stabilize the well wall; (4) It can be used in various applications and can block micro-fractures and relatively large fractures; (5) The gel plugging agent has good compatibility with the formation [9][10][11]. It will not affect the formation environment.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, polymer gel plugging agent is an important branch of chemical gel plugging agent, compared with general plugging materials. The advantages are obvious, with: (1) low density is beneficial to the protection of oil and gas reservoirs; (2) gelling time is controllable, and the controllable time range is large, which is convenient for it to accurately reach the missing layer for plugging; (3) plugging The leaking slurry has strong fluid loss performance, and the formation of filter cakes can help stabilize the well wall; (4) It can be used in various applications and can block micro-fractures and relatively large fractures; (5) The gel plugging agent has good compatibility with the formation [9][10][11]. It will not affect the formation environment.…”
Section: Introductionmentioning
confidence: 99%
“…Then the gel is injected into the downhole to improve the bear capacity of the reservoir and form a plugging layer that contributes to the fluid loss control. Gamage et al 15 revealed a polymer gel as fluid-loss control pill for well control during completion operations in high-temperature reservoirs. The pill is formulated by synthetic watersoluble polymers and metal crosslinkers in monovalent high-density brine.…”
Section: Introductionmentioning
confidence: 99%